O FMI mudou? Uma análise de sua atuação no caso da Grécia, no contexto da atual crise financeira mundial - Bromerschenkel, Ricardo (2012)
The Institution International Monetary Fund (IMF) has been accused, mostly from the 1980s, to be of service of developed nations, particularly to the United States, to impose on developing countries ideologies of the Washington Consensus. Criticisms have broken out both from academics and the general and economics press. It has also been criticized by academics to impose contractionary policies on developing countries, already in recession, worsening recessionary, while in developed countries have been applied expansionary policies to stimulate economic growth and job creation (Keynesian policies). In addition to external criticism, the very Institution (IMF) has recognized that some of its instruments, such as fiscal policies, should be reviewed in view of the severity of the economic contraction of the Asian countries, where these policies were applied. This suggests changes in the Institution’s future policies, as a response to academic criticism and by its own recognition of the need for transformation. It was found that the performance in the World Financial and Economic Crisis of 2008/2009 the IMF acted as lender of last resort, providing liquidity to developing and poor countries, the same policies recommended to developing countries. These expansionary policies were adopted to cope with the global recession of 2009. However, in the particular case of Greece, a Eurozone peripheral country, in financial insolvency stat, the Institution (IMF) returned to the same contractionary policy of the past decades and the early 2000s. We conclude, therefore, that the IMF has not changed its macro policy assistance programs to countries in financial crisis, as in the current case of Greece, in relation to those applied to indebted countries in the past. The IMF didn’t charge.